Principles of Antibiotic Prophylaxis in Total Joint Arthroplasty: Current Concepts. Issue 8 (August 2015) - Bosco, Joseph A.; Bookman, Jared; Slover, James; Edusei, Emmanuel; Levine, Brett
Abstract : Infection is a rare, serious complication following total joint arthroplasty and constitutes a considerable emotional and financial burden for patients, surgeons, and healthcare systems. Prevention of surgical site and periprosthetic joint infections is crucial. This requires knowledge of the microorganisms that commonly cause these infections, including Staphylococcus species. Selection of the appropriate antibiotic regimen to treat infection remains controversial, but cefazolin and cefuroxime are the most commonly recommended antibiotics for prophylaxis. Appropriate timing of administration before surgery, with redosing performed as needed, can help to ensure optimal antibiotic concentration during surgery. Given the increasing evidence that S aureus colonization is a risk factor for periprosthetic joint infection, an exploration of the potential benefits of preoperative S aureus carrier screening and decolonization protocols is warranted. The use of antibiotic-loaded bone cement in primary total joint arthroplasty and antibiotic powder at wound closure are other controversial topics that require additional research.